please solve this and give full explanation
Attachments:
![](https://hi-static.z-dn.net/files/dae/4a3a96e092062e119b6f502b8b17c1bd.jpg)
Answers
Answered by
2
we know sum of roots is -(-p)/5
Alfa + beta = p/5
Alfa - beta = 1
adding both we get 2×alfa = (p+5)/5
p = 10×alfa - 5
or subtracting the equations
2beta = (p-5)/5
p = 10beta + 5
Alfa + beta = p/5
Alfa - beta = 1
adding both we get 2×alfa = (p+5)/5
p = 10×alfa - 5
or subtracting the equations
2beta = (p-5)/5
p = 10beta + 5
Similar questions
English,
9 months ago
Political Science,
9 months ago
Hindi,
1 year ago
Math,
1 year ago
Chemistry,
1 year ago
CBSE BOARD X,
1 year ago